Amniotic Band Syndrome: A Silent Knife In-Utero - Fatema, N.; Acharya, Yogesh; Yaqoubi, H.N.A. (Nepal Medical College Journal, 2019)
Amniotic band syndrome (ABS) is a rare, but serious congenital syndrome complex. It is associated with a wide range of fetal structural anomalies, notably craniofacial and limb anomalies. Early prenatal diagnosis is important to provide accurate information to the parents, predict the prognosis and in some cases perform in-utero lysis of the bands to restore the blood flow to the affected limb. A postnatal multidisciplinary approach involving vascular decompression, reconstructive surgery, prosthesis, and physiotherapy are some of the therapeutic options. It is necessary to consider ABS in prenatal screening with a high index of suspicion as early screening can allow a timely therapeutic strategy and reduce the severity of the associated defects.